Drawing the body in: A comic essay on trans mobility and materiality - Councilor, KC (Women's Studies in Communication, 2018)
This comic essay engages trans embodiment and temporality, representation and identity, passing, and drawing as a form of thinking. Although uncommon, comics have been established in academia as a genre worthy of literary study as well as scholarly inquiry in the broader humanities, social sciences, and the arts (Bukatman, 2012; Chute, 2010; Howard & Jackson, 2013; Cox, 2016). Recently, scholars have also studied the use of comics making as an analytical tool in qualitative research (Katz, 2013; Sousanis, 2015; Weaver-Hightower, 2013; Flowers, 2017; Henningsen, 2017; Johnson, 2018). This comic essay invites communication scholars to consider transgender embodiment and mobility through a visual medium that can illustrate complex problems of precarity, passing, and the crossing of both material and symbolic borders and boundaries. As a genre, comics allow for dense and layered information to be conveyed very quickly, and its affordances lend themselves well to portraying the tensions in and between trans and gender-nonconforming experiences. The speech bubble and the thought bubble, for example, can juxtapose in a single panel what two characters are saying to one another and what they are thinking and feeling as well as how they are interacting and communicating non-verbally. This graphic scholarship demonstrates why the unique genre of comics is particularly apt in rendering instances of microagression or passing. I argue that comics as a form enable a shift from abstract concepts back into the body, the materiality of which can get lost in academic discourse.
Keywords: Comic essay; dept.com; embodiment; mobility; transgender

Applying an integrative technology adoption paradigm to health app adoption and use - Dam, Linda; Roy, Deya; Atkin, David J.; Rogers, Dana (Journal of Broadcasting & Electronic Media, 2018)
The present study employs an audience-centered approach to examine motivations for mobile fitness app use. We explicate and test an Integrated Technology Adoption model, which incorporates perspectives on competition, self-esteem, self-efficacy, and audience uses and gratifications. An online survey of 469 respondents reveals that app adoption intentions were predicted by internal competition orientations and gratifications, exercise self-efficacy, social utility motives, and attitudes toward the app. External competition decreased behavioral intentions related to app use. Study results thus provide support for an integrative model linking social cognitive factors with a new set of mobile app uses and gratifications.
Keywords: dept.com; peer-reviewed